George Thacher papers - Thacher, George, 1754-1824.
Handwritten transcripts of letters (1790-1792) from Thacher to his wife, Sarah Savage Thacher, Biddeford, District of Maine, Me.. regarding family matters; ALS (1789 July 9; New York, N.Y.) from Thacher to William Taylor, a merchant of Baltimore, Md., regarding commercial policy discussed in Congress; and one letter (1789 March 29) to Thacher from John Avery regarding the first Congress and financial matters.
In part, handwritten transcripts.
U.S. representative from Massachusetts (1787, 1789-1801) and associate judge, Massachusetts Supreme Court and Maine Supreme Court.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Avery, John, -- 1739-1806 -- Correspondence; Taylor, William, -- active 1789 -- Correspondence; Thacher, Sarah Savage -- Correspondence; United States. -- Congress -- 1789-1791).; Biddeford (Me.) -- Social life and customs; Massachusetts -- Politics and government -- 1775-1865.; United States -- Commercial policy; United States -- Politics and government -- 1783-1809.; Jurists; Representatives, U.S. Congress -- Massachusetts